Characterization of a natural substituted pyromorphite - Botto, Irma Lía (1997)
Pyromorphite (Pb5(PO4)3Cl) which occurs in the oxidation zone of a polymetallic Pb–Zn–Ag–Au vein in Paramillos de Uspallata, Mendoza, Argentina, was studied by scanning electron microscopy (including energy dispersive analysis of X-rays (EDAX) electron microprobe), i.r. and Raman spectroscopies and X-ray powder diffraction analysis. The substitution of Pb by Ca and Ba and Cl by OH, respectively, have been detected. In addition, i.r. absorption bands for the CO2-3 ν3-mode have been clearly identified. They are attributed to the CO2-3 for PO-34 substitution in the structure. The composition is regarded as an indication of the paragenesis of the host rocks and the mineralogy of the deposit.